2020
DOI: 10.1111/apt.16023
|View full text |Cite
|
Sign up to set email alerts
|

Review article: pathophysiology and management of primary biliary cholangitis

Abstract: SummaryBackgroundPrimary biliary cholangitis (PBC), an immune‐mediated disease characterised by destruction of intrahepatic bile ducts, results in progressive damage to the biliary tree, cholestasis and ultimately advanced liver disease. In the last decade, advances in practice have improved clinical care, driven novel therapeutic options and improved risk stratification tools.AimsTo provide an overview of the disease characteristics of PBC and review a patient‐centred management approach for the clinical team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 154 publications
(194 reference statements)
0
18
0
10
Order By: Relevance
“…Besides UDCA and obeticholic acid, 24-norursodeoxycholic acid (norUDCA) is also used to treat PSC and cholestasis liver diseases with favorable outcomes ( Fickert et al, 2013 ; Fickert et al, 2017 ). Unfortunately, 40% of patients do not have a satisfactory response to UDCA and are at risk of cirrhosis or non-neoplastic complications ( Leung et al, 2020 ; Wagner and Fickert, 2020 ). The results of the present study demonstrated that BDL could lead to the accumulation of serum TBA and TC which induce a significant liver injury, as evidenced by the increasing of serum ALT, AST, ALP, GGT and hepatic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides UDCA and obeticholic acid, 24-norursodeoxycholic acid (norUDCA) is also used to treat PSC and cholestasis liver diseases with favorable outcomes ( Fickert et al, 2013 ; Fickert et al, 2017 ). Unfortunately, 40% of patients do not have a satisfactory response to UDCA and are at risk of cirrhosis or non-neoplastic complications ( Leung et al, 2020 ; Wagner and Fickert, 2020 ). The results of the present study demonstrated that BDL could lead to the accumulation of serum TBA and TC which induce a significant liver injury, as evidenced by the increasing of serum ALT, AST, ALP, GGT and hepatic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…PBC is an autoimmune disease characterized by destruction of intrahepatic bile ducts which results in progressive damage to the biliary tree, cholestasis and ultimately advanced liver disease [ 14 ]. Patients with autoimmune disorders seem to have an elevated risk of lymphoma, especially non-Hodgkin's lymphoma [ 2 , 3 , [11] , [12] , [13] ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with autoimmune disorders seem to have an elevated risk of lymphoma, especially non-Hodgkin's lymphoma [ 2 , 3 , [11] , [12] , [13] ]. For PBC patients, advances in practice have currently improved clinical care, driven novel therapeutic options and developed risk stratification tools [ 14 ], though a number of immunosuppressants may not be associated with clinical benefit [ 2 , 3 ]. The use of more potent immunomodulatory agents may raise concerns over the risk of adverse effects including the development of non-Hodgkin's lymphoma [ 2 , 3 , [11] , [12] , [13] ].…”
Section: Discussionmentioning
confidence: 99%
“…PBC is a chronic liver disease, with immune mediated injury to biliary epithelial cells and represents an interaction between genetic and environmental factors [57]. Prevalence ranges from 19.1 (Australia) to 40.2 (USA) cases per million persons.…”
Section: Primary Biliary Cholangitismentioning
confidence: 99%